2020
DOI: 10.12944/crnfsj.8.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-treatment in Producing Pumpkin Powder Using Air Fryer and Its Application in 'Bingka' Baking

Abstract: Pumpkin powder is one of the main pumpkin products with longer shelf life and it can act as a substitute for pumpkin flesh in different types of formulated foods. This work focused on producing pumpkin powder from different pumpkin parts and evaluating the effects of powder substitution on the physical properties of cake (bingka). Different parts of pumpkin (peeled, unpeeled, and skin) were pre-treated by soaking in limewater solution and then dried in an air fryer at the temperature of 80 °C, 120 min and air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Similarly, Murzaini et al. (2020), reported that pretreatment of pumpkin had a significant effect on the particle size of pumpkin powder.…”
Section: Resultsmentioning
confidence: 86%
“…Similarly, Murzaini et al. (2020), reported that pretreatment of pumpkin had a significant effect on the particle size of pumpkin powder.…”
Section: Resultsmentioning
confidence: 86%
“…However, moisture content for all samples was above 50%. To date, the highest moisture content obtained for 'bingka' is 45.92% (Murzaini et al, 2020). Apart from other ingredients, the amount of durian paste used also has resulted to an increment in moisture content.…”
Section: Moisture Contentmentioning
confidence: 99%
“…The industrial food applications of pumpkins also include meat products (beef meatballs, chicken burgers, and low-fat meatballs), grain products (bread, cake, biscuits, cookies, muffins, and pasta), beverages (juice, pineapple juice, and smoothies), and dairy (yoghurt and ice cream) [1,[8][9][10]. It can also be incorporated into foods such as candies and rice cakes, as well as the traditional Indonesian cake 'Bingka' [11,12]. Enriching food products with pumpkin can be considered a strategy to increase the consumption of vegetables and the bioactive ingredients present in them without significantly changing eating habits of the population [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%